New Developments in Osteoarthritis Treatment – Focus on Biologic Agents - José Ignacio Torrero; Carlos Martínez; Ignacio Torrero (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Osteoarthritis (OA) is one of the most common diseases around the world. As the world population ages, osteoarthritis (OA) becomes a disease with physical and economic consequences for both patients and communities. Medical, social, and financial consequences oblige clinicians, surgeons, and researchers to focus on finding the best treatment option, to eradicate and stop this degenerative joint disease, and to avoid surgical options which in many instances are over-indicated. OA is a complex disease involving cartilage degradation leading finally to bone-on-bone contact with loss of articular balance and strength and episodes of inflammation. Knee, hip, ankle, and foot joints are the most frequent to suffer OA because of their relevance as weight-bearing joints. Noninvasive treatments, such as anti-inflammatory drugs, physiotherapy, orthotic devices, dietary supplements, have demonstrated a lack of effectiveness. The possibility to perform intra-articular injections with hyaluronic acid, corticosteroids, or the newest but criticized treatment based on platelet-rich plasma (PRP) has changed the management of OA disease. PRP allows the possibility of repairing the damage of joint cartilage, prevents degeneration, reduces pain, and accelerates joint functionality. The use of PRP has led to many differences in treatment since there is a lack of consensus about protocols, indications, number of doses, cost-effectiveness, and duration of the treatment. Many publications have suggested efficacy in tendon injuries, but when PRP has been indicated to treat cartilage injuries, things are more inconsistent. Some authors have reported their experience treating OA with PRP, and it seems that, if well indicated, it is an option as a supplementary therapy. Therefore, we need to understand that OA is a mechanical disease that not only produces changes in radiographs but also affects the quality of life. The Pathogenesis of OA has been well explained, providing us with new knowledge and future possibilities to improve the clinical approach. From basic science to surgery, there is a great field we all need to contribute to, because the general population is aging, and total joint replacements should not be the only solution for OA. So herein is an actual review of the developments for treating OA with biologics, intended to be useful for the population inside orthopedics who could be called bio-orthopedists, since OA is a molecular homeostasis disbalance between catabolism and anabolism triggered by mechanical stress.